The ideal of beauty in the building of recognition marks in ocularcentric societies: the building of the body in blind women in Metropolitan Area in Monterrey - Brenda Araceli Bustos García (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
The aim of this paper is around the question: How do the blind women build the body image? Are they influenced by the hegemonic discourse of the ideal of beauty? At first we define the characteristics of an ocularcentric society. Than once we make a deconstruction of empirical research about the body building in blind women. Finally we present our proposed analysis, relying on narrative psychology, developing a perspective that interprets the building body in blind women as a narrative act through which marks recognition are used to evaluate and classify something as beautiful and attractive. In the analysis of the interviews we found that building of recognition marks has two variables: a) one in which certain distrusts and even rejections in the opinions generated is shown by using senses such as smell , touch, etc. (b) Other one in which a concept is constructed: tactile aesthetics. Distrust or acceptance of aesthetic tactile is generated mainly by aspects such as: (a) age at which they lost the sight (b) job they do (c) blindness condition time.